Corvus: an automatic Raven's-like test generator - Thimbleby, IJ (2018)
The primary focus of this thesis is the development of an automatic Raven’s-like test generator, called Corvus. Corvus was designed to be capable of investigating the relative validity of repeat testing for Raven’s Standard Progressive Matrices (SPM). Raven’s SPM is often considered a ‘Gold Standard’ for general intelligence testing. However, following studies conducted using Corvus, this thesis found evidence that Raven’s SPM lacks validity as a measure of intelligence on repeat testing. Specifically that retesting with Raven’s SPM resulted in the tests losing correlation between item difficulty and time taken per item, while maintaining participant rank order (Spearman’s ρ, n = 53).